Perjanjian Kemitraan Ekonomi Antara Indonesia Jepang - Lara Fitri Yani Simarmata; Gressia Sitanggang; Tamaulina Br. Sembiring (Jurnal Multidisiplin Indonesia, 2024)
In 2007, Indonesia and Japan signed an Economic Partnership Agreement called the Indonesia-Japan Economic Partnership Agreement (IJEPA). This agreement is an important step in strengthening economic relations between the two countries. IJEPA aims to increase trade and investment between Indonesia and Japan by eliminating or reducing trade barriers such as tariffs on goods and encouraging cooperation in various economic fields. With IJEPA, both countries are committed to facilitating the flow of goods and services between them through trade liberalization. Apart from that, this agreement also includes cooperation in the field of investment, protection of intellectual property rights, and strengthening cooperation in terms of technology and human resource development. Since it was signed, IJEPA has provided many benefits for both parties, increasing the volume of trade and investment between Indonesia and Japan and opens up opportunities for wider cooperation in various economic sectors. I wrote this article to analyze the impact and implications of IJEPA for the economic development of the two countries. Through a qualitative approach, this article investigates the effects of IJEPA on trade volume, investment and economic growth in Indonesia and Japan.